LA GRANJA INTEGRAL AUTOSUFICIENTE: ESTRATEGIA EDUCATIVA DE DESARROLLO SOSTENIBLE EN EL SECTOR RURAL - Herrera Acosta, Daniel (Tecné, Episteme y Didaxis: TED, 1998)
This paper s a reflection about the advantages of a farm as educational resource. Also, it presents the idea of the farm as a base of the human development for the Colombian farmer The Universidad Pedagógica Nacional plays an important role in order to seek that the farm could be used as a laboratory where the child finds enough tools to improve his life conditions, The farm has the property of joining people in order to rise some social values as solidarity, good communication, tolerance, respect, etc. which are the fundamentals of social development. Besides, the farm Iets farmers recognize the level of resources that they have, and doing a good use of them thinking about the future. Finally it is important to say that the farm will help the child to identify the different changes of energy and how important are those process for keeping his own resources